2016
DOI: 10.7717/peerj.2404
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenolic secondary metabolites fromSchotia brachypetalaSond. (Fabaceae) and demonstration of their antioxidant activities inCaenorhabditis elegans

Abstract: BackgroundSchotia brachypetala Sond. (Fabaceae) is an endemic tree of Southern Africa whose phytochemistry and pharmacology were slightly studied. The present work aimed at profiling the major phenolics compounds present in the hydro-alcohol extract from S. brachypetala leaves (SBE) using LC/HRESI/MS/MS and NMR and prove their antioxidant capabilities using novel methods.MethodsIn vitro assays; DPPH, TEAC persulfate decolorizing kinetic and FRAP assays, and in vivo assays: Caenorhabditis elegans strains mainte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 53 publications
4
22
0
Order By: Relevance
“…In vitro antioxidant activities of the bark extract were determined using two commonly assays DPPH (2,2-diphenyl-1-picrylhydrazyl radical) and FRAP [ 43 ] following the protocol described by [ 44 ]. In brief, DPPH scavenging capacity assay was done following the standard assay reported by Blois [ 45 ] with some modifications adapted to a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In vitro antioxidant activities of the bark extract were determined using two commonly assays DPPH (2,2-diphenyl-1-picrylhydrazyl radical) and FRAP [ 43 ] following the protocol described by [ 44 ]. In brief, DPPH scavenging capacity assay was done following the standard assay reported by Blois [ 45 ] with some modifications adapted to a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the total phenolic content was estimated by the Folin-Ciocalteu method as described before [ 44 ]. In brief, a stock solution (2.5 mg/mL of the lyophilized extract) was prepared.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Demir et al, 2017a). In previous studies, Fabaceae family have been shown to be rich in phenolics, such as gallic acid, fumaric acid, chlorogenic acid, 4-hydroxybenzoic acid, caffeic acid, cinnamic acid, p-coumaric acid, catechin derivatives, quercetin, hesperidin, taxifolin, naringenin, myricetin, resveratrol, apigenin, and galangin (Sobeh et al, 2016;Bencherchar et al, 2017). There have been numerous reports of the selective cytotoxic effects of these phenolics on different cancer cells (Ravishankar et al, 2013;Anantharaju et al, 2016).…”
Section: Resultsmentioning
confidence: 98%